Enhancing Employee Performance : The Role of Leadership Style and Communication - Uki Yonda Asepta; Budi Eko Soetjipto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research examines the impact of leadership style and communication on staff performance within an energy sector organization in Madura. The primary problem addressed is the need to understand how different leadership attributes and communication effectiveness impact employee productivity and satisfaction. In today’s competitive business environment, effective leadership and communication are essential for achieving organizational goals and fostering a motivated workforce. The objective of the study is to identify key indicators of leadership and communication that contribute to enhanced employee performance, thereby providing actionable insights for organizational improvement. A quantitative survey method was employed, utilizing a structured questionnaire with Likert scale items to gather data from 50 employees. This approach allowed for the collection of measurable data regarding employee perceptions of their leaders' styles and communication effectiveness. The analysis revealed that communication skills and the ability to control subordinates were rated highest by respondents, indicating satisfaction in these areas. However, lower ratings for motivational ability and emotional control suggest areas for improvement, highlighting the need for leaders to develop these critical skills further. The findings support the hypothesis that effective leadership and communication are critical for fostering a productive work environment, with significant implications for organizational success. The study concludes that organizations should prioritize leadership development and communication training to enhance employee engagement and performance. Limitations include the focus on a single industry, suggesting the need for further research across diverse sectors to validate these findings and explore their long-term impact on organizational outcomes. Future studies could also investigate the interplay between leadership styles and employee performance over time, providing deeper insights into effective management practices.